Politeness Strategies In Youtube Comment In Catatan Najwa Eps. Melawan Stigma Corona - Sucitra, Sucitra (Journal of Asian Multicultural Research for Social Sciences Study, 2020)
The purpose of this research was to find politeness strategies used by netizens in YouTube comments section based on Najwa Shihab’s YouTube Channel. This research was descriptive qualitative research based on politeness strategies phenomena in written language. Thirteenth strategies found in this research were expressing wish and gratitude, intensifying support and interest, softening request, being pessimistic, giving sympathy, using identity marker, being indirect, showing agreement, face-negative threatening acts, giving questions or asking reason, using impersonal forms, using joke, and giving praise. The data in this research used verbal impressions of netizens comments on Najwa Shihab YouTube Channel period April 2020. This research used the principle of courtesy Brown Levinson to classify and analyze the data according to its category. This research also was found that the obidience of positive face and threaten positive face are more dominant. These kinds of utterance are dominant in netizens comment is influenced by context.